The influence of multimedia in teaching languages - Arabic language as a study - Elbiary, Yousef A. Baker; Ali Hassan, Elsayed Makki Elbishr; Elhag, Ibrahim Babikir; Suleiman, Hassan; Isa, Koussoube (Turkish Physiotherapy Association, 2022)
Modern technologies today have become the basis of human life, and their uses have reached all areas of life. The use of modern technologies has also been greatly employed in education, especially in language learning. The Arabic language is one of the most important languages that native speakers and non-native speakers are interested in learning. Teaching languages using modern technologies and multimedia included all aspects of language such as composition, classification, classrooms and teaching methods. The aim of the study is to highlight the importance of modern educational technologies and multimedia in the field of Arabic language teaching and make it an important and indispensable basis for teaching Arabic and an integral part of the mechanisms used in teaching Arabic and a role model in its teaching methods.